ਪੌਦਾ ਰੋਗ ਵਿਗਿਆਨ - Singh, Amerjit (Punjab Agricultural University Ludhiana Punjab, 2014)
The book gives information on the causes and effects of various types of plant disease.
Pauda Roga Vigyan
Keywords: Punjabi; ਪੌਦਾ ਰੋਗ ਵਿਗਿਆਨ; Pauda Roga Vigyan; Plant Pathology; Punjabi; Punjabi